2023
DOI: 10.18280/isi.280227
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Multi-Organization E-Government Based on Hyperledger Fabric Blockchain Platform

Osama I. Kadhum,
Ali H. Hamad

Abstract: E-governments can face various security problems due to the nature of online systems and the sensitive information they handle. Some of these security issues include: cyberattacks, data breaches, Identity theft, access control, and many others. Permissioned blockchain is one of the cutting-edge technologies that can help to reduce the impact of security vulnerabilities of e-governments. In this work, six organizations as a case study have adopted, two scenarios performed to analyze the performance of hyperledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In Kadhum & Hamad (2023) it is conclude, through the analysis of two scenarios, that the performance of a blockchain network is influenced by hardware and software configurations, the complexity of smart contracts, and the scale of the organization.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kadhum & Hamad (2023) it is conclude, through the analysis of two scenarios, that the performance of a blockchain network is influenced by hardware and software configurations, the complexity of smart contracts, and the scale of the organization.…”
Section: Related Workmentioning
confidence: 99%
“…The functioning of blockchain is recognized as a technology capable of providing a transparent and secure platform resistant to unauthorized storage and sharing of information. The idea is to utilize smart contracts for automating the delivery of government services, ensuring they are delivered in a secure and transparent manner, which is crucial for public administration (Kadhum & Hamad, 2023).…”
Section: Application Of Blockchain Technology In E-governmentmentioning
confidence: 99%
“…Blockchain-based e-Government or Blockchain-based governance refers to the integration of resources and system integration between internal government business systems and parallel or subordinate external functional departments into a convenient, high-quality, affordable one-stop service for the public and businesses to complete parallel approvals, execute transparent, clean, and efficient online administrative management system operations, In Figure 8, it can be observed that in the context of e-Government, it is connected with government (G2G), business (G2B), education (G2E), and the public (G2C). Therefore, Figure 9 explains that the architecture and scenarios of e-Government using Blockchain technology aim to protect data and information from security breaches that could lead to financial and emotional losses for the public [67].…”
Section: Appropriate Blockchain Applications For Governmentmentioning
confidence: 99%